Pengaruh latihan fisik terhadap kepadatan matrik tulang atlet remaja wanita - Elfia Rosyida, (Ilmu Keolahragaan, 2013)
Abstract : Exercise may be the most important  environmental factor that can increase peak bone mass. Adequate estrogen levels are necessary for maintenance ofbone strenght. The bone mass of puberty female athlete decrease because of chronic physical activity. Status of estrogen in puberty periode has highest level, but it can decrease because of chronic physical activity. This article use methode by searching data from Pubmed with keyword  physical training,exercise, adolescent female,estrogen,growth, bone , dan epiphyseal plate. Hard physical activity give overload for bone especially can caused injury in epiphyseal cartilage.Extremes of exercise training produce negative effects on bone owing to decreases in estrogen. Low level of estrogen can not maintenance integrity of bone. . Key word : physical training,  exercise,  adolescent female, estrogen, growth,  bone , epiphyseal plate